2014
DOI: 10.1177/1358863x14549270
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of calcification in carotid endarterectomy tissues: Comparison of micro-computed tomography imaging with histology

Abstract: Calcified plaque is heterogeneously distributed in CEA tissues with most in the bulb and IES regions. The amount of calcification in micro-CT slices shows a high correlation with matched histology sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The histological analyses showed, for both decalcified and undecalcified samples, a stratified structure supporting the pathological etiology of atherosclerotic plaques and reflecting the literature description of soft tissue samples (17)(18)(19)(20). In particular, the semi-thin decalcified samples stained in H&E showed a clear picture of the stratification in both autopsy and cemeterial samples (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The histological analyses showed, for both decalcified and undecalcified samples, a stratified structure supporting the pathological etiology of atherosclerotic plaques and reflecting the literature description of soft tissue samples (17)(18)(19)(20). In particular, the semi-thin decalcified samples stained in H&E showed a clear picture of the stratification in both autopsy and cemeterial samples (Fig.…”
Section: Resultssupporting
confidence: 80%
“…It may be present in the lumen as a calcified plaque cap or may also invade the intima or media [ 10 ]. It has been shown that the amount of calcification quantified by carotid CT correlated with respective histology sections [ 11 , 12 ]. Carotid US is an easy and economically favorable method to study different plaque features and their potential association with symptoms [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, conventional histological sectioning can induce tears and folds in arterial tissue, and in the specific case of large arteries, often causes separation of the collagen-rich adventitia from the external elastic lamina [ 70 ]. In heavily calcified blood vessels such as those found next to extensive lipid-rich atherosclerotic plaques, calcified deposits are also prone to “drop out” of the arterial wall when sectioned, producing shearing artefacts and tissue damage ( Figure 2 A) [ 71 , 72 ]. This precludes the accurate quantification of calcification using image analysis tools such as Image J.…”
Section: Commonly Used Methods To Quantify Vascular Calcification mentioning
confidence: 99%